Festival and special event management - Allen, Johnny; O'Toole, William;McDonnell, Ian;Harris, Robert (Australia : John Wiley & Son, Inc., 2005)
This textbook attempts to capture and refine this emerging body of knowledge, and to document it in a useful form for both researchers and practitioners in this field.
Part 1 : Event context -- Part 2 : Event strategy -- Part 3 : Event management -- Part 4 : Trends and issues
Includes bibliographical references and index.
Keywords: FESTIVALS -- MANAGEMENT